Reading Concept Map-Think Pair Share (Remap-TPS) Learning Model on Cognitive Ability and Scientific Attitude - Jatmiko, Agus; Kartina, Yesilia; Irwandani, Irwandani; Fakhri, Jamal; Pricilia, Agitha; Rahayu, Titik (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2018)
The recent integration of learning models in the learning process has become the focus of science education experts, especially in Indonesia, such as the adoption of the Reading-Concept Map Think Pair Share (Remap TPS) learning model. This study aims to improve the students’ cognitive abilities, and scientific attitudes through the Reading-Concept Map Think Pair Share model. The study was conducted to junior high school students by employing Quasi-experimental with Non-equivalent Control Group Design. The instruments used were multiple choice tests and observation sheets. The result of the research shows that the students’ cognitive ability is in the medium category with an N-gain value of 0.47. Based on this result, it can be concluded that the Remap TPS learning influences the students’ cognitive ability. The obtained average percentage score of the students’ scientific attitudes is 81.76% which belongs to the very good category. Thus, it can be concluded that this study provides important implications for educators to be more creative in designing learning models in order to improve the students’ cognitive abilities and scientific attitudes.